PRODUKTIVITAS DAN PENDAPATAN USAHA TANI UBI KAYU (MANIHOT UTILISIMA) DI DESA TUNGKARAN KABUPATEN BANJAR - Fenny Refiana; Eddy Triatmoko; Subhan Fitriadi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
The purpose of this research is to know the revenue, the explicit cost, income and productivity of cassava variety sulawesi. This research was conducted in March – May 2021 at Tungkaran village Banjar regency. The simple random sampling method used was by observing 21  farmers in Tungkaran village who planted Cassava. The average result of the revenue is Rp. 2.468.142,86/farmer, the average explicit cost is Rp. 961.413,50/farmer, and average income Rp. 1.506.729,36/farmer and productivity 14,43 Ton/Ha. From this result of development of farming cassava sulawesi variety we believe that it has good prospect and revenue, of the average income, technical and economically